Minimization of product defects by the means of implementing correct test pyramid in the software development process - Giorgadze, L.; Alibiev, D.; De Chirico, G.; Kazhikenova, A.Sh. (Bulletin of the Karaganda University. Mathematics Series, 2017)
Article attempts to present one of the solutions towards the problem of flawed and delayed product development. The history behind current most popular product development methodology (waterfall methodology) is traced, as well the problems that this methodology presents such as calendar risks or high employee turnover rate. The methodology that was created to solve those issues is gaining a lot of popularity now, because it offers much more agile way of delivering a software product by splitting the whole development process into manageable iterations. Customer can change the requirements and adapt the product to the market changes from iteration to iteration. However, this new methodology (agile methodology) presents some serious problems as well. This article concentrates tackles the main issue - insurance of the product quality with each iteration. The solution that is presented by the article revolves around creating and maintaining a correct test pyramid, with the specific description of all the layers of the pyramid. A small study was conducted on a sample project, where it was calculated, that test pyramid allowed to decrease the amount of defects by 25 %.